Temperature below a gliding cross country ski - Schindelwig, K.; Hasler, M.; Van Putten, J.; Rohm, S.; Nachbauer, W. (Procedia Engineering, 2014)
The temperature of snow under skating skis was studied with infrared sensors at four positions and three different velocities. To have an indication of causes and consequences of the heating the friction coefficient with a linear tribometer and the pressure distribution were measured as well. The friction increased with velocity. The highest temperature increase was measured 440 mm from the ski end at the highest velocity of 10 m/s. Temperature increase at position 1550 mm was independent of velocity. Friction coefficient, pressure distribution and temperature measurements showed a high reliability and allowed to create a model to explain the temperature profile along the ski.